Revolta do Buzu: Transporte Público e Direito Social, em Salvador - 2003 - MENEZES, Dirla Mara dos Santos (2017)
This study aims to analyze the impacts of the Revolta do Buzu (Revolt of Buzu, in reference to buses), which happened in 2003, in the city of Salvador. An important social movement that emerged from the increase in the rates charged for urban buses, this movement had an effective participation of the students of the capital of Bahia, demanding an improvement in the quality of public transport services. The crowds that paralyzed the city for several days transformed the local public transport system and revealed the importance of popular uprisings to guarantee citizens' rights. Reflected in other capitals, the Revolta do Buzu (Revolt of Buzu) can be considered as one of the collective actions that effectively transformed Brazilian public transport into social right. In order to achieve the objective proposed in this study, an exploratory research was developed, which adopted the deductive method for qualitative analyzes that were based on data collected from different sources.